2019
DOI: 10.1088/1367-2630/ab022d
|View full text |Cite
|
Sign up to set email alerts
|

The multilayer structure of corporate networks

Abstract: Various company interactions can be described by networks, for instance the ownership networks and the board membership networks. To understand the ecosystem of companies, these interactions cannot be seen in isolation. For this purpose we construct a new multiplex network of interactions between companies in Germany and in the United Kingdom, combining ownership links, social ties through joint board directors, R&D collaborations and stock correlations in one linked multiplex dataset. We describe the features… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In particular, we build a multiplex network consisting in a collection of M = 24 layers, one for each GICS sector. While all layers are composed of the same nodes (countries), the connections within each layer are based on the links between countries for the respective industry sector, preserving in this way the sectoral multi-layered nature of the country-to-country interactions [ 71 , 72 ].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In particular, we build a multiplex network consisting in a collection of M = 24 layers, one for each GICS sector. While all layers are composed of the same nodes (countries), the connections within each layer are based on the links between countries for the respective industry sector, preserving in this way the sectoral multi-layered nature of the country-to-country interactions [ 71 , 72 ].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The results show that just 0.61% of the top shareholders accumulate 80% of the control over the value of all firms in the network. In the study by Jeude, Aste, and Caldarelli (2019) conducted in February 2018, it is possible to note that the multiplex network of German and British corporations represent different types of corporate control relations: R&D alliances, board interlocking, ownership links, and mutual cross-shareholder. Among the results found by the authors is the relationship between corporate performance and the centrality of these firms in the multiplex network.…”
Section: Corporate Control and Networkmentioning
confidence: 99%
“…Multiplex networks 76,77 provide a natural framework to describe such relationships and first empirical studies have shown that different layers are not structurally similar. Examples include: credit and liquidity exposures in the UK interbank market 78 , payments and exposures in the Mexican banking system 60 , the Mexican interbank market 79 , the Italian interbank market 80 , Colombian financial institutions and market infrastructures 81 , the EU derivatives market 28 , the UK interest rate, foreign exchange, and credit derivatives market 47 , corporate networks 82 . Several works have focused on financial contagion on multiplex networks, see Section 3.3.…”
Section: Multiplex and Higher-order Networkmentioning
confidence: 99%